A modified bias-extension test method for the characterisation of intra-ply shear deformability of hybrid metal-composite laminates. (15th June 2023) - Liu, Shichen; Sinke, Jos; Dransfeld, Clemens
Abstract: The bias-extension test is one of the test methods to characterise the intra-ply shear behaviour of continuous fibre reinforced composites including fabrics and unidirectional (UD) materials. For the determination of the major mechanical properties of metals, often a uniaxial tensile test is used. Combination of these two methods for the shear deformation of hybrid metal-composite laminates is proposed comparing the method for cross-plied unidirectional prepregs and woven fabric prepregs. The effects of material constituent, shear rate, preheat temperature and normal pressure on the intra-ply shear behaviour are investigated. The results indicate that the material constituents and the frictional responses depending on processing parameters play a critical role in the shear characterisation of the hybrid laminate. The shear angle measurement at four typical strains demonstrates that the support of metal layers improves the shear deformability by delaying the onset of fibre wrinkling. This modified intra-ply shear test contributes to a better understanding of the process design for wet (uncured) hybrid metal-composite laminate manufacturing.